Method for measuring uniformity of glass batch
The uniformity of the glass compound material was detected by the vibrating screen method, which solved the problems of complex detection and large errors in the prior art, and achieved simple and fast uniformity evaluation, which was suitable for a wide range of glass compound materials.
Patent Information
- Application Number
- CN202411430613.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-07
AI Technical Summary
When detecting the uniformity of glass mixing materials in the prior art, the conductivity method and acid-base titration method have complex operation, slow analysis speed, large errors and are only suitable for specific types of glass mixing materials, and cannot fully reflect uniformity.
Using the vibrating screen method, the glass mixing material is screened and the relative percentage on each layer of screen is calculated, the optimal screen combination is determined, and the uniformity test is performed randomly. The average cumulative results and relative percentage difference of the sampled samples are calculated, and the uniformity is evaluated. sex.
It realizes the simplicity, fast, scientific, objective and accurate detection of the uniformity of glass mixing materials, and has a wide range of application, avoids deviations from existing methods, and provides a more comprehensive and accurate uniformity reflection.
Smart Images

Figure QLYQS_2 
Figure QLYQS_3 
Figure QLYQS_4
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass production, and in particular to a method for measuring the uniformity of glass batch materials. Background Art
[0002] In the glass production process, in order to ensure the quality and stability of glass products, preparing high-quality batch materials is one of the important processes of glass production, and the uniformity of the batch materials is one of the key indicators reflecting the quality of glass batch materials. At present, the methods generally adopted by glass manufacturing enterprises to detect the uniformity of glass batch materials are: conductivity method and acid-base titration method.
[0003] The principle of the conductivity method is that salt compounds such as soda ash (sodium carbonate) in the glass batch can be completely dissolved and ionized in water. The charged particles in this type of electrolyte solution will move and transfer electrons under the influence of electric potential, showing conductive properties. The conductivity value of the solution obtained after the batch sample is dissolved in water is measured, and the uniformity is calculated according to the difference in conductivity. This method reflects the uniformity of the overall batch by measuring the uniformity of specific components soluble in water in the batch, which is not accurate enough. The key point of the acid-base titration method is to dissolve the batch sample in water, use the acid-base titration principle, add methyl orange indicator and titrate with hydrochloric acid standard solution, and the solution changes from yellow to orange, which is the end point. It can be seen that the acid-base titration obtains the uniformity value by measuring the content of sodium carbonate and potassium carbonate, but this method is complicated to operate, slow to analyze, and the titration end point is not easy to observe, and there are errors. At the same time, the above two methods are only applicable to the detection of the uniformity of glass batches containing soda ash and water-soluble inorganic salts. Summary of the invention
[0004] The present invention provides a method for measuring the uniformity of glass batch materials, which can not only solve the problems of partial generalization and lack of objectivity in the analysis of the prior art methods mentioned in the above technical background, but also provides a method with strong applicability, simple sample processing, simple operation, fast and scientific measurement and calculation, and can objectively and accurately reflect the uniformity of glass batch materials.
[0005] Based on the above purpose, the technical solution adopted by the present invention is:
[0006] A method for measuring the uniformity of a glass batch material comprises the following steps:
[0007] S1. Weigh each raw material according to the required proportion of each raw material, so that the total weight of the batch is M 标总 ;
[0008] S2. Add the weighed raw materials together and mix them evenly to obtain a uniformly mixed batch, and use the uniformly mixed batch as a standard reference sample;
[0009] S3, put the whole set of sieves into the vibrating sieve machine in the order from coarse to fine from top to bottom;
[0010] S4, placing the remaining batch material from S2 on the top sieve and using a suitable cover, fixing it, starting the vibrating sieve machine, and setting the vibrating sieve machine working time;
[0011] S5. After the vibrating screen machine stops working, remove each layer of sieves one by one, clean the batch material particles left on each sieve with an appropriate brush, and weigh them with a balance to record the weight of the batch material left on each layer of sieve. The weight of the standard batch material left on the top sieve is recorded as M. 标1 The weight of the remaining batch material on the screen is recorded as M 标i , calculate the relative percentage W of the batch material left on each screen except the top screen 标i ,
[0012]
[0013] S6. Select adjacent and corresponding W 标i The sieve combination with the sum closest to 22-25% is the best sieve group;
[0014] S7. Randomly take a weight of M at the appropriate position where the batch material is about to enter the kiln. 待测总 The glass batch material sample to be tested;
[0015] S8, install the top screen in step S3 in the vibrating screen machine, install the best screen group confirmed in step S6 below the top screen, place the batch material to be tested in step 7 on the top screen and use a suitable cover, after fixing, start the vibrating screen machine, and set the vibrating screen machine working time;
[0016] S9, repeat step S5, record the weight of the tested batch material left on the top sieve and each sieve of the best sieve combination for each sample, wherein the weight of the glass batch material to be tested sample left on the top sieve is recorded as M 待测1 , the weight of the tested batch remaining on each layer of the sieve is M xi , calculate the relative percentage W of the tested batch material left on each layer of the best sieve group for each sample 待测i ,
[0017]
[0018] S10, calculate the cumulative relative percentage X of each sample in the best sieve group i ,
[0019] X i =ΣW to be measured i;
[0020] S11. Calculate the average cumulative result of all sampled samples, recorded as ACR, the formula is as follows:
[0021]
[0022] n: the number of samples drawn;
[0023] X i : Cumulative relative percentage of a single sample in the best sieve group (%);
[0024] S12, the cumulative relative percentage of each sample in the best sieve group X i Compare with the average cumulative result (ACR), calculate the absolute value of the difference between ACR and the relative percentage of a single sample, and record it as ABS.
[0025]
[0026] in,
[0027] ABS ≥ 2% poor uniformity,
[0028] 1%≤ABS<2%Acceptable uniformity,
[0029] ABS<1% for best uniformity.
[0030] Furthermore, M in step S1 and step S7 标总 and M 待测总 The value range is 200g~400g.
[0031] Furthermore, in steps S1, S5, S7, and S9, the weighing balance must be accurate to two decimal places, that is, the sensitivity is ±0.01g.
[0032] Further, in step S3, the specifications of the full set of sieves and the order from top to bottom are: 2360 -1180-841-595-425-300-212-180 -150-125 -106-90 -75-63 -53-45 -38, all in microns.
[0033] Furthermore, in step S4, the working time of the vibrating screen machine is set to 15 to 30 minutes.
[0034] Furthermore, in step S7, samples are taken at the position of the screw feeder, 20 to 30 samples are taken each time, the sampling interval of each sample is 5 minutes, and each sample is numbered.
[0035] Furthermore, in step S8, the working time of the vibrating screen is set to 5 to 10 minutes.
[0036] Furthermore, when a suitable brush is used to clean the residual particles on each screen in step S5, it is best to clean the particles from the back of the screen first to prevent the screen from being expanded.
[0037] Furthermore, the optimal screen group consists of 3 to 5 screens.
[0038] In summary, the method of the present invention is simple and easy to operate, and avoids the disadvantage of generalizing the uniformity of the titration method or the conductivity method by using a specific component soluble in water. At the same time, the sample processing of the present invention is simple, no grinding is required, and a lot of time and labor costs are saved. It is not necessary to screen the standard reference sample every time. Only when there are major changes in raw materials and material ratios, it is necessary to reconfigure the standard sample and select the best screen. The calculation is scientific and simple, can fully reflect the uniformity of the batch, has a wide range of applications, and helps technicians understand the degree of homogenization of the batch, and provides data support for material adjustment and stable production. DETAILED DESCRIPTION
[0039] The technical solution of the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Embodiment 1:
[0041] A method for determining the uniformity of glass batch materials, the process is as follows:
[0042] (1) Sampling: Collect enough raw materials from each raw material silo, and according to the glass formula, theoretically calculate and weigh the appropriate weight of each raw material (the balance is accurate to two decimal places) to obtain about 320g of batch material (including broken glass), and mix it in a mixer for 10 minutes to fully mix and obtain a standard reference sample of the batch material (the value of the uniformity of the mixture is determined by the chemical titration method, 20g is used for the chemical titration method to determine the uniformity of the mixture, and 300g is used as the standard reference sample for the uniformity of the mixture tested by this screening method).
[0043] (2) Install the screens in the correct order from top to bottom in Table 1, and add the total weight of 300g (M 标总 ) is placed on the first layer of sieve and covered with a suitable cover. After fixing, the vibrating sieve machine is started to vibrate for 30 minutes;
[0044] (3) After the vibrating screen machine stops working, remove each layer of the sieve one by one, clean the batch material particles left on each sieve with an appropriate brush, and weigh them with a balance (±0.01g). Record the weight of the batch material left on each layer of the sieve, where the weight of the standard batch material left on the top sieve is recorded as M. 标1 The weight of the remaining batch material on the screen is recorded as M 标i , calculate the relative percentage W of the batch material left on each screen except the top screen 标i ,
[0045] The experimental data are as follows:
[0046] The mass of the standard reference sample of the batch material is 300.0 g, M 标1 =72.08g, the total mass under the 2360μm sieve is 227.92g, that is, M 标总 -M 标1 =227.92g.
[0047] Table 1
[0048]
[0049] Note: + before the number indicates the material on the sieve, - indicates the material under the sieve.
[0050] (4) Select the best sieve combination (usually 3 to 5 sieves), that is, select the sieve combination with the corresponding cumulative result closest to 22-25% as the best sieve group. According to the experimental results in Table 1, select the sieve closest to 22-25%, that is, the three sieves with the specifications of 125-106-90 (μm) as the best sieves, and record the results;
[0051] (5) The material for monitoring the uniformity of the batch is obtained from the position of the screw feeder. You can also choose to randomly select a piece of material at the discharge port of the glass mixer and take a sample once every 5 minutes, about 500g each time. A total of 24 batch samples are taken for testing, and all samples are numbered from 1 to 24.
[0052] (6) Weigh out about 300 g of each of the 24 batch materials to be tested, record their weights, and use a sieve with a specification of 2360 μm and three sieves with the above-mentioned optimal sieve specifications of 125 μm-106 μm-90 μm to fix them on the sieve bottom plate in the order of 2360 μm-125 μm-106 μm-90 μm from top to bottom, cover the lid, fix it on the vibrating sieve machine, and start the vibrating sieve machine for 5 minutes;
[0053] (7) After the vibrating screen machine is finished, remove each layer of the screen one by one, and use a suitable brush to clean the small amount of material particles left on each screen. Use a balance (±0.01g) to weigh the weight of the material remaining on the 2360μm screen and each layer of the best screen group. The weight of the glass batch sample to be tested remaining on the 2360μm screen is recorded as M. 待测1 , the weight of the tested batch remaining on each layer of the sieve is Mx i , calculate the relative percentage W of the tested batch material left on each layer of the best sieve group for each sample 待测i ,
[0054]
[0055] (8) Calculate the cumulative percentage X of each sampled batch on the best confirmed sieve i ,
[0056] X i =∑W to be measured i;
[0057] (9) Calculate the average cumulative result (ACR) associated with all sampled items using the formula:
[0058]
[0059] According to the experimental data, the ACR of this example is 26.54%.
[0060] (10) In order to evaluate the analytical results of the homogeneity of the tested batch, it is necessary to compare the individual sampling results with the average cumulative result (ACR), calculate the difference between the ACR and the individual samples, and calculate the absolute value of each difference (ABS).
[0061] See Table 2 for specific data;
[0062] if:
[0063] ABS ≥ 2% means poor uniformity (check the mixing process), 1% ≤ ABS < 2% means acceptable uniformity, and ABS < 1% means the best uniformity.
[0064] Table 2: Batch uniformity test data
[0065]
[0066]
[0067] Data analysis: In combination with this embodiment, such as the relevant data in Table 2, in the uniformity requirement of this test data, the ABS value is <1%, indicating that the homogenization degree of the batch is good.
[0068] Data on batch uniformity testing using acid-base titration:
[0069] Acid-Base Titration Test Method
[0070] Weigh 20.0000g of the mixture from the prepared standard reference sample and each sample to be tested, add it to a beaker and heat it with 100mL pure water to dissolve it, filter it into a 500mL volumetric flask with quick filter paper, wash the beaker and precipitate more than 5 times, and make up to volume. Accurately take 50.00mL from the volumetric flask into a 300mL conical flask, add water to 100mL, add 2 drops of indicator methyl orange (1wt%), and titrate with a 0.05mol / L hydrochloric acid standard solution. The end point is when the solution changes from yellow to orange. Calculate the sodium carbonate equivalent through the consumption of hydrochloric acid, and calculate the uniformity value of the batch through the formula.
[0071] Average hydrochloric acid consumption
[0072]
[0073] X 盐酸i : The amount of hydrochloric acid consumed by each sample to be tested.
[0074] n: the number of samples drawn from the spiral feeding port;
[0075] Standard Deviation:
[0076]
[0077] The uniformity of the batch material is:
[0078]
[0079] Since the calculation process is consistent, the volume of hydrochloric acid consumed is directly used for calculation. The mass of the batch material used for titration is
[0080] =20 / 500*50=5g.
[0081] The standard sample was tested by chemical titration method, consuming 32.2 mL of hydrochloric acid (0.05 mol / L), and the corresponding sodium carbonate equivalent was 0.000805 mol.
[0082] Table 3: Chemical titration test batch uniformity data (hydrochloric acid concentration 0.05 mol / L)
[0083]
[0084] Through the chemical titration test of 24 samples in this batch, the uniformity value of this batch is 98.1003%, which is far less than the qualified standard of more than 95.0%. The uniformity of this batch is qualified. Compared with the standard reference sample, the amount of hydrochloric acid consumed by chemical titration is similar to the average value of this batch, which also shows that the uniformity of this batch is relatively good.
[0085] Comparison of the two groups of data analysis of qualified uniformity: In the requirements of uniformity data tested by the screening method, the ABS value is <1%, indicating that the batch is well homogenized.
[0086] The uniformity of this batch of materials was tested using chemical titration, and the test result was 98.1003%, which exceeded the uniformity qualified standard value (≥95.0%). However, this method is complicated to operate, slow to analyze, and the titration endpoint is difficult to observe, which is prone to errors.
[0087] In general, the test results of the glass batch material by screening method are consistent with the test results of the chemical titration method. Comparing the two methods, the screening method for testing glass batch material is simpler, more convenient, and has a fast test speed; the chemical titration method is more complicated, the process is long, and it is easy to produce large errors.
[0088] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for determining the uniformity of a glass batch material, characterized in that: The following steps are involved: S1. Weigh each raw material according to the required proportion of each raw material, so that the total weight of the batch is M 标总 ; S2. Add the weighed raw materials together and mix them evenly to obtain a uniformly mixed batch, and use the uniformly mixed batch as a standard reference sample; S3, put the whole set of sieves into the vibrating sieve machine in the order from coarse to fine from top to bottom; S4, placing the remaining batch material from S2 on the top sieve and using a suitable cover, fixing it, starting the vibrating sieve machine, and setting the working time of the vibrating sieve machine; S5. After the vibrating screen machine stops working, remove each layer of sieves one by one, clean the batch material particles left on each sieve with an appropriate brush, and weigh them with a balance to record the weight of the batch material left on each layer of sieve. The weight of the standard batch material left on the top sieve is recorded as M. 标1 The weight of the remaining batch material on the screen is recorded as M 标i , calculate the relative percentage W of the batch material left on each screen except the top screen 标i , ; S6. Select adjacent and corresponding W 标i The sieve combination with the sum closest to 22-25% is the best sieve group; S7. Randomly take a weight of M at the appropriate position where the batch material is about to enter the kiln. 待测总 The glass batch material sample to be tested; S8, install the top screen in step S3 in the vibrating screen machine, install the best screen group confirmed in step S6 below the top screen, place the batch material to be tested in step 7 on the top screen and use a suitable cover, after fixing, start the vibrating screen machine, and set the vibrating screen machine working time; S9, repeat step S5, record the weight of the tested batch material left on the top sieve and each sieve of the best sieve combination for each sample, wherein the weight of the glass batch material to be tested sample left on the top sieve is recorded as M 待测1 , the weight of the tested batch remaining on each layer of the sieve is M xi , calculate the relative percentage W of the tested batch material left on each layer of the best sieve group for each sample 待测i , ; S10, calculate the cumulative relative percentage X of each sample in the best sieve group i , ; S11. Calculate the average cumulative result of all sampled samples, recorded as ACR, the formula is as follows: n: the number of samples drawn; X i : The cumulative relative percentage of a single sample in the best sieve group (%); S12, the cumulative relative percentage of each sample in the best sieve group X i Compare with the average cumulative result (ACR), calculate the absolute value of the difference between ACR and the relative percentage of a single sample, and record it as ABS. ; in, ABS ≥ 2% Poor uniformity, 1% ≤ ABS < 2% Acceptable uniformity, ABS <1% Optimal uniformity.
2. The method for measuring the uniformity of a glass batch material according to claim 1, characterized in that: M in step S1 and step S7 标总 and M 待测总 The value range is 200g~400g.
3. The method for measuring the uniformity of a glass batch material according to claim 1, characterized in that: In steps S1, S5, S7, and S9, the weighing balance must be accurate to two decimal places, that is, the sensitivity is ±0.01g.
4. The method for measuring the uniformity of a glass batch material according to claim 1, characterized in that: In step S3, the specifications of the full set of sieves and the order from top to bottom are: 2360 -1180 - 841 - 595 -425 -300 -212 - 180 -150 - 125 -106 - 90 -75 - 63 -53 - 45 -38, and the unit is: micron.
5. The method for measuring the uniformity of glass batch materials according to claim 1, characterized in that: In step S4, the vibrating screen machine working time is set to 15-30 min.
6. The method for measuring the uniformity of glass batch materials according to claim 1, characterized in that: In step S7, samples are taken at the position of the screw feeder, 20 to 30 samples are taken each time, the sampling interval of each sample is 5 minutes, and each sample is numbered.
7. The method for measuring the uniformity of glass batch materials according to claim 1, characterized in that: In step S8, the vibrating screen machine working time is set to 5 to 10 minutes.
8. The method for measuring the uniformity of glass batch materials according to claim 1, characterized in that: The best screen group consists of 3 to 5 screens.